Uses and benefits of algae as a nutritional supplement for honey bees - Nichols, Benjamin J.; Ricigliano, Vincent A. (Frontiers in Sustainable Food Systems, 2022)
Honey bees are essential agricultural pollinators that are threatened by various interacting stressors, posing risks to beekeeping industries and human food security. Malnutrition is a major factor underlying managed bee colony losses that can be countered by feeding artificial diets, which aim to deliver essential macro- and micronutrients. Current bee nutritional supplements show room for improvement and require resources that compete with human food production. Algae and microalgae in particular have been gaining traction in the literature as alternative feed sources and nutritional supplements for livestock, including honey bees. Herein, we review the current literature and categorize the effects of algae supplementation on honey bee colony productivity as well as effects on individual bee physiology and health. In general, we conclude that algae biomass appears to be suitable for use as a bee feed additive and as a source of health-stimulating natural products. Additionally, we suggest research areas that could improve the development of sustainable algae-based nutrition supplements for honey bees.